The impact of gender and sex in psoriasis: What to be aware of when treating women with psoriasis. Issue 2 (13th April 2022) - Guillet, Carole; Seeli, Corsin; Nina, Meienberger; Maul, Lara Valeska; Maul, Julia-Tatjana
Abstract : Background: Psoriasis is a common chronic inflammatory skin disease with an exceptionally high burden for women. Objective: Sex-dependent differences in disease manifestation, severity, treatment choices, subjective disease perception, and the impact on quality of life and risk factors are described and comprehensively discussed. Methods: A literature search was conducted using MEDLINE (PubMed) and the Cochrane Library for systematic reviews to investigate the challenges in treating women with psoriasis. Results and conclusions: The incidence, prevalence, and manifestation of psoriasis of the skin are similar between different sexes. Genetic and environmental factors such as obesity and metabolic syndrome are risk factors and are not equally relevant or pronounced in women and men. Overall, women have a lower disease severity measured by the Psoriasis Area Severity Index, which is associated with a higher impairment of their life quality measured by the Dermatology Life Quality Index compared with men. In addition, women with psoriasis are more likely to have depression than men. Hormonal factors affect psoriasis, with a correlation of high estrogen levels and improvement of psoriasis. Data regarding differences in prescribing patterns of systemic treatments and the severity of psoriasis are not entirely consistent. Registry studies show that men tend to have more severe psoriasis and, in some cases, are prescribed systemic therapies more frequently. Women tend to respond better to systemic treatments and to experience more adverse events. Treatment options are the same for both sexes, except during pregnancy and lactation. Various treatment options are contraindicated due to fear of fetal or neonate harm and lack of data. Topical steroids can be prescribed with a high degree of safety during pregnancy. For other topical therapies (calcineurin inhibitors and vitamin D analogs), no studies of adverse effects in pregnancy are available, and safety data mainly stem from studies examining effects after systemic administration. Antitumor necrosis factor monoclonal antibodies (except for certolizumab pegol) have been associated with a possible increased risk of preterm birth, low gestational age, and cesarean deliveries. Prospective data on the safety of biologics other than antitumor necrosis factor-alpha antibodies to accurately assess whether novel biologics (eg, anti-interleukin 17, 12/23, 23) can be used for systemic therapy in pregnancy are lacking or currently being conducted.